THE HISTORY, ACHIEVEMENTS, PERSPECTIVES OF TRACK TEST BRANCH RESEARCH LABORATORY OF DNIPROPETROVSK NATIONAL UNIVERSITY OF RAILWAY TRANSPORT NAMED AFTER ACADEMICIAN V. LAZARYAN - Rybkin, V. V.; Moiseienko, K. V. (Science and Transport Progress, 2003)
The history and the basic research directions of Branch track testing research laboratory ofDnepropetrovsk national university of railway transport named after academician V. Lazarjan are given in the article.